The Representation of Different Genders in Product Advertising: Comparison of TV Advertisements in Thailand and the United Kingdom - Tadpikultong, Supavee (2008)
With the strong impact of advertising to the business by which it could limit or expand the perception of customer towards the product and the organisation, the marketing strategists then wonder on how to cope with gender role portrayal in advertising; especially within the television advertising which are watched from most of the family members. Until now there are extensive researches on the issue of gender roles in advertising which were trying to support the debates about differential portrayal of the two genders in international television advertisements. However, these researches were mostly focused on the North American commercials and only a few from the following countries; China, Singapore, Australia, Mexico, Malaysia, France, and the UK.